Tourism Destination Maturity and the Influence of Political Instability: The Case of Cyprus - Pitsillides, Ioannis (2008)
Traditionally tourism was the research subject of a significant amount of studies. However, in recent years due to the rising competition for inbound tourists between countries all over the world, tourism has received much more academic attention and its future growth has become a talking point amongst analysts and researchers. Competition in the tourism industry is intense due to the fact that for a lot of countries tourism is vital for injecting large amounts of money in their economies, and for offering the opportunity for direct or indirect employment in the industry for millions of people. Cyprus, a traditional Mediterranean tourism destination, is part of the group of countries that heavily rely on the success of its tourism industry. Despite the constant growth of its tourism industry since the 1980s, Cyprus has recently experienced a decline in tourist arrivals. Due to the importance of tourism on the prosper growth of the economy of Cyprus this study will initially investigate whether Cyprus is still an emerging tourism destination, or perhaps it has moved in a maturity stage. Moreover, a cross-community comparison will be made, aiming to uncover the effects of the political instability on the tourism industries of the Greek-Cypriot and Turkish-Cypriot communities. In order to examine these two issues a questionnaire survey will be employed. After analysing the results certain conclusions are drawn. The results reject that Cyprus is a mature destination but emphasise on the bad shape of the Cypriot tourism sector. This thesis also concludes that the political instability in Cyprus affects the tourism product of the two communities in a negative way. Research also provides a number of recommendations for the tourism stakeholders in Cyprus and the general public.